Quinolinic acid/tryptophan ratios predict neurological disease in SIV-infected macaques and remain elevated in the brain under cART - Drewes, Julia L. (J Neurovirol, 2015)
Activation of the kynurenine pathway (KP) of tryptophan catabolism likely contributes to HIV-associated neurological disorders. However, KP activation in brain tissue during HIV infection has been understudied, and the effect of combination anti-retroviral therapy (cART) on KP induction in the brain is unknown. To examine these questions, tryptophan, kynurenine, 3-hydroxykynurenine, quinolinic acid, and serotonin levels were measured longitudinally during SIV infection in striatum and CSF from untreated and cART-treated pigtailed macaques. mRNA levels of KP enzymes also were measured in striatum. In untreated macaques, elevations in KP metabolites coincided with transcriptional induction of upstream enzymes in the KP. Striatal KP induction was also temporally associated - but did not directly correlate - with serotonin losses in the brain. CSF quinolinic acid/tryptophan ratios were found to be the earliest predictor of neurological disease in untreated SIV-infected macaques, outperforming other KP metabolites as well as the putative biomarkers Interleukin-6 (IL-6) and Monocyte chemoattractant protein-1 (MCP-1). Finally, cART did not restore KP metabolites to control levels in striatum despite control of virus, though CSF metabolite levels were normalized in most animals. Overall these results demonstrate that cerebral KP activation is only partially resolved with cART, and that CSF QUIN/TRP ratios are an early, predictive biomarker of CNS disease.